2012
DOI: 10.1007/s00228-011-1206-1
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of prophylactic cefoxitin in patients undergoing colorectal surgery

Abstract: To ensure cefoxitin target concentrations during surgery, we recommend that cefoxitin be administered every 1.5 h in patients with a CL(CR) ≥ 60 mL/min and every hour if the CL(CR) is ≥ 100 mL/min. Administration by continuous infusion preceded by a bolus injection should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…dose (24); this half-life is slightly prolonged compared to that previously reported for nonobese adults (35). Despite administration of substantially higher doses, the mean C max observed in the present study was similar to concentrations previously reported for other populations, including nonobese adults receiving fixed cefoxitin doses (24,33,37). This decreased C max /D ratio and the prolonged half-life are both consistent with a 2-fold-higher V observed in this study compared to that reported for nonobese individuals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…dose (24); this half-life is slightly prolonged compared to that previously reported for nonobese adults (35). Despite administration of substantially higher doses, the mean C max observed in the present study was similar to concentrations previously reported for other populations, including nonobese adults receiving fixed cefoxitin doses (24,33,37). This decreased C max /D ratio and the prolonged half-life are both consistent with a 2-fold-higher V observed in this study compared to that reported for nonobese individuals.…”
Section: Discussionsupporting
confidence: 86%
“…Five thousand simulations were performed at each MIC and for each of the selected pathogens. For pharmacodynamic evaluation of free (unbound) drug levels, the approximate free fraction of cefoxitin in human blood (average, 0.30; range, 0.21 to 0.48) was incorporated into Monte Carlo simulations to obtain corresponding pharmacodynamic parameters for free drug (fTϾMIC) (33). The targeted pharmacodynamic goal was the cefoxitin concentration above the MIC of these common pathogens (TϾMIC) for 100% of the prophylactic dosing interval (i.e., fTϾMIC ϭ 100%) as suggested by previous literature (34).…”
Section: Methodsmentioning
confidence: 99%
“…Despite antibiotic prophylaxis, subtherapeutic tissue antibiotic concentrations are observed in obese patients and may facilitate wound infection. 35, 36 . In addition, the development of wound infection may be enhanced by an attenuated inflammatory response secondary to endotoxin tolerance in obese patients 37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, exposure of antimicrobials that are eliminated mainly in urine, such as cephalosporins, is higher in patients with renal insufficiency than in patients with normal renal function [26,27] and therefore the probability to reach the pharmacodynamic target significantly increases. This means that patients with normal renal function have more risk of underdosage.…”
Section: Organismmentioning
confidence: 99%